Post-Operative Acute Urinary Retention After Greenlight Laser. Analysis of Risk Factors from A Multicentric Database: Predicting Factors of Post-Operative Acute Urinary Retention After Greenlight Laser - Campobasso, Davide; Acampora, Anna; De Nunzio, Cosimo; Greco, Francesco; Marchioni, Michele; Destefanis, Paolo; Altieri, Vincenzo; Bergamaschi, Franco; Fasolis, Giuseppe; Varvello, Francesco; Voce, Salvatore; Palmieri, Fabiano; et al. (Urology Journal, 2021)
Purpose: Greenlight laser is a mini-invasive technique used to treat Benign Prostatic Obstruction (BPO). Some of the advantages of GreenLight photoselective vaporization (PVP) are shorter catheterization time and hospital stay compared to TURP. Post-operative acute urinary retention (pAUR) leads to patients' discomfort, prolonged hospital stay and increased health care costs. We analyzed risk factors for urinary retention after GreenLight laser PVP. Materials and Methods: In a multicenter experience, we retrospectively analyzed the onset of early and late post-operative acute urinary retention in patients undergoing standard or anatomical PVP. The pre-, intra- and post-operative characteristics were compared betweene patients who started to void and the patients who developed post-operative urinary retention. Results: The study included 434 patients suitable for the study. Post-operative acute urinary retention occurred in 39 (9%). Patients with a lower prostate volume (P < .001), an adenoma volume lower than 40 mL (P < .001), and lower lasing time (P = .013) had a higher probability to develop pAUR at the univariate analysis. The multivariate logistic regression confirmed that lower lasing time (95% CI: 0.86-0.99, OR = 0.93, P = .046) and adenoma volume (95% CI: 0.89–0.98, OR = 0.94, P = .006) are correlated to pAUR. Furthermore IPSS ≥ 19 (95% CI: 1.19- 10.75, OR = 2.27, P = .023) and treatment with 5-ARI (95% CI: 1.05-15.03, OR = 3.98, P = .042) are risk factors for pAUR. Conclusion: In our series, post-operative acute urinary retention was related to low adenoma volume and lasing time, pre-operative IPSS ≥ 19 and 5-ARI intake. These data should be considered in deciding the best timing for urethral catheters removal.